Alternative Splicing of SMPD1 in Human Sepsis - Kramer, Marcel (PLoS One, 2015)
Acid sphingomyelinase (ASM or sphingomyelin phosphodiesterase, SMPD) activity engages a critical role for regulation of immune response and development of organ failure in critically ill patients. Beside genetic variation in the human gene encoding ASM (SMPD1), alternative splicing of the mRNA is involved in regulation of enzymatic activity. Here we show that the patterns of alternatively spliced SMPD1 transcripts are significantly different in patients with systemic inflammatory response syndrome and severe sepsis/septic shock compared to control subjects allowing discrimination of respective disease entity. The different splicing patterns might contribute to the better understanding of the pathophysiology of human sepsis.